2007
DOI: 10.1253/circj.71.688
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Levels of Plasma Free Dopamine With Future Coronary Events in Patients With Coronary Artery Disease

Abstract: Background There is an intimate relationship between activation of the sympathetic nervous system and myocardial ischemia. This study examined whether plasma levels of dopamine, a precursor of norepinephrine, may provide prognostic information in coronary artery disease (CAD). Methods and ResultsPlasma levels of free dopamine were measured by high-performance liquid chromatography in 210 consecutive patients with stable CAD. The patients were prospectively followed up for a period of ≤36 months until occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Increased sympathetic activity has proven to be detrimental in CAD. 16 Current therapy in ischemic heart disease has mainly focused on shielding the β-adrenergic receptor from high sympathetic tone. Although effective, this solves only part of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sympathetic activity has proven to be detrimental in CAD. 16 Current therapy in ischemic heart disease has mainly focused on shielding the β-adrenergic receptor from high sympathetic tone. Although effective, this solves only part of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a positive correlation of dopamine levels with CAC, and some have demonstrated negative correlation of CAC with dopamine levels. 30,65 Studies have also shown a positive and a negative association of dopamine blood levels with hypertension which is another risk factor for CAC. 66,67 Dopamine exerts its cardioprotective effect and prevent coronary artery calcium formation by inhibiting the norepinephrine release, reducing pancreatic insulin production and by decreasing the activity of lymphocytes.…”
Section: L) Hormones (Norepinephrine Cortisol and Dopamine)mentioning
confidence: 99%
“…On the other hand, human immunodeficiency virus (HIV) infection results dopaminergic dysfunction that alters DA levels . Furthermore, plasma levels of DA give preindication for cardiovascular events in patients with coronary artery disease . Thus, the determination of DA levels in biological samples is of paramount importance for researchers and chemical analysts.…”
Section: Introductionmentioning
confidence: 99%